Wind energy explained : theory, design and application. - Manwell, James F., ....-; McGowan, Jon G., ....-; Rogers, Anthony L., 1948- (Chichester : Wiley, 2009)
Wind energy's bestselling textbook- fully revised.This must-have second edition includes up-to-date data, diagrams, illustrations and thorough new material on: the fundamentals of wind turbine aerodynamics; wind turbine testing and modelling; wind turbine design standards; offshore wind energy; special purpose applications, such as energy storage and fuel production.Fifty additional homework problems and a new appendix on data processing make this comprehensive edition perfect for engineering students.This book offers a complete examination of one of the most promising sources of renewable energy and is a great introduction to this cross-disciplinary field for practising engineers."provides a wealth of information and is an excellent reference book for people interested in the subject of wind energy.
Keywords: Windenergie